The Role of Nutritional Status in Improving Physical Endurance in Athletes: A Literature Review - Sandi, Samrian; Syahara, Sayuti; Firdaus, Kamal; Donie, Donie; Rahman, Dally; Zarya, Fiky (JURNAL INFO KESEHATAN, 2024)
In the context of modern sports science, understanding the profound impact of nutritional status on athletic performance has become increasingly crucial. This study aims to review the existing literature regarding the role of nutritional status in increasing the physical endurance of athletes. Optimal nutritional status plays an important role in supporting athletic performance through mechanisms involving nutrient intake, energy metabolism, and post-workout recovery. Various studies show that malnutrition can result in decreased physical ability, increased risk of injury, and slow recovery. Conversely, adequate nutrition can improve muscle strength, cardiovascular endurance, and metabolic efficiency. This article summarizes the key findings from various studies that highlight the importance of macro and micro nutrition, hydration, and proper diet planning in supporting athletes' physical endurance. The conclusion of this review underscores that nutritional strategies tailored to the individual needs of athletes are essential to achieve optimal performance and minimize the risk of injury. More research is needed to explore the complex interactions between various nutritional factors and physical fitness components.